A Development Strategy of Tailor-made Natural Deep Eutectic Solvents for the Enhanced Extraction of Hydroxynaphthoquinones from Alkanna tinctoria Roots - Bossard, Elodie; Tsafantakis, Nikolaos; Aligiannis, Nektarios; Fokialakis, Nikolas (Planta Medica, 2022)
Natural hydroxynaphthoquinone enantiomers (HNQs) are well-described pharmaceutical and cosmeceutical agents especially present in the roots of Alkanna tinctoria (L.) Tausch, a species native to the Mediterranean region. In this work, eco-friendly natural deep eutectic solvents (NaDESs) were developed for the selective extraction of these compounds. An extensive screening was performed using more than sixty tailor-made NaDESs. The impact of the intrinsic physicochemical properties on the HNQs extraction efficiency as well as the specificity towards the different enantiomeric pairs was thoroughly investigated. As a result of a multivariate analysis and of the one factor-a-time solvent optimization, the eutectic mixture composed of levulinic acid and glucose (LeG) using a molar ratio of 5 : 1 (molHBA : molHBD) and 20% of water (w/w) was found as the most appropriate mixture for the highest extraction efficiency of HNQs. Further optimization of the extraction process was attained by response surface methodology, using a temperature of 45 °C, a solid-to-liquid ratio of 30 mg/mL, and an extraction time of 50 min. A maximum extraction output of 41.72 ± 1.04 mg/g was reached for HNQs, comparable to that of the commonly used organic solvents. A solid-phase extraction step was also proposed for the recovery of HNQs and for NaDESs recycling. Our results revealed NaDESs as a highly customizable class of green solvents with remarkable capabilities for the extraction of HNQs.
Keywords: Natural Deep Eutectic Solvent (NaDES); eco-friendly; Alkanna tinctoria; Boraginaceae; hydroxynaphthoquinone enantiomers